The relationship between free-throw accuracy and performance variables in male wheelchair basketball players - Shigematsu, S.; Ogawa, M.; Neya, M.; Fujiwara, M.; Nakata, H. (Journal of Human Sport & Exercise, 2022)
We investigated the relationship between the free-throw accuracy and performance variables among fourteen elite male wheelchair basketball players. Participants performed 20 basketball free-throws. Basketball performance variables were the phases of the pre-shoot routine: (a) time taken, (b) minimum angle when taking the ball back, (c) angle at ball release, (d) angular displacement during the forward arm swing, and (e) angular velocity at ball release on the elbow, shoulder, and hip. A significant negative correlation was observed between the free-throw accuracy and mean pre-shot time, suggesting that participants with a shorter pre-shot time showed a higher free-throw accuracy. In addition, a significant negative correlation was found between the free-throw accuracy and variability of angular velocity of the hip at the time of ball release, indicating that the consistency of hip movement is an important factor in free-throw accuracy. In contrast, there were no relationship between the free-throw accuracy and player`s classification point defined as International Wheelchair Basketball Federation, and experience of wheelchair basketball. These data suggest that the routine duration and trunk movement are related to free-throw accuracy in wheelchair basketball.